POSITIVE SELF-PRESENTATION OF AHOK AT KEPULAUAN SERIBU - Al Fatah, Muhammad Yusuf; Chojimah, Nurul; Khasanah, Ismatul (Department of Language and Literature, Faculty of Cultural Studies, Universitas Brawijaya, 2020)
This research attempted to discover the positive self-presentation built by Ahok as the speaker and the former of DKI Jakarta governor through his speech in front of Kepulauan Seribu residents. It is done by applying Fairclough’s CDA involving conventional implicature, positive connotation, speech act, and political communication. The result of the study shown that there were eight positive characters representing positive self-presentation found in the study which suggested that Ahok had a firm, simple, wise, discipline, fair, caring, positive thinking, and confident personality. The Firmness was manifested in nine data, the simplicity appeared in two data, the wisdom occurred in ten data, the discipline revealed in three data, the fairness were presented in three data, the care was realized in two data, the positive thinking come up in one datum, and the confidence appeared in four data. Thus from those finding, it could be drawn as the conclusion that firmness and wisdom were the positive-self presentations mostly delivered by Ahok in his speech.